Staging/typing of Lewy body related α-synuclein pathology: a study of the BrainNet Europe Consortium - Alafuzoff, I; Ince, P; Arzberger, T; Al-Sarraj, S; Bell, J; Bodi, I; Bogdanovic, N; Bugiani, O; Ferrer, I; Gelpi, E; Gentleman, S; Giaccone, G; et al. (Springer-Verlag, 2009)
When 22 members of the BrainNet Europe (BNE) consortium assessed 31 cases with α-synuclein (αS) immunoreactive (IR) pathology applying the consensus protocol described by McKeith and colleagues in 2005, the inter-observer agreement was 80%, being lowest in the limbic category (73%). When applying the staging protocol described by Braak and colleagues in 2003, agreement was only 65%, and in some cases as low as 36%. When modifications of these strategies, i.e., McKeith’s protocol by Leverenz and colleagues from 2009, Braak’s staging by Müller and colleagues from 2005 were applied then the agreement increased to 78 and 82%, respectively. In both of these modifications, a reduced number of anatomical regions/blocks are assessed and still in a substantial number of cases, the inter-observer agreement differed significantly. Over 80% agreement in both typing and staging of αS pathology could be achieved when applying a new protocol, jointly designed by the BNE consortium. The BNE-protocol assessing αS-IR lesions in nine blocks offered advantages over the previous modified protocols because the agreement between the 22 observers was over 80% in most cases. Furthermore, in the BNE-protocol, the αS pathology is assessed as being present or absent and thus the quality of staining and the assessment of the severity of αS-IR pathology do not alter the inter-observer agreement, contrary to other assessment strategies. To reach these high agreement rates an entity of amygdala-predominant category was incorporated. In conclusion, here we report a protocol for assessing αS pathology that can achieve a high inter-observer agreement for both the assignment to brainstem, limbic, neocortical and amygdala-predominant categories of synucleinopathy and the Braak stages